Internal septa of the maxillary sinus and their significance in the planning of endodontic interventions, sinus lifting and dental implantation using a collagen matrix scaffold - I. A. Gatilo; S. V. Sirak; V. N. Lenev; A. V. Arutyunov; N. Bykova; I. I. Kartashevsky; D. Y. Polyakova (Эндодонтия Today, 2024)
INTRODUCTION. The study of the structure of the septa in the area of the maxillary sinus floor is important when planning implantation and sinus lifting operations. The height, number and location of the septa can affect the course of the sinus lifting operation. The aim is to study the structure of the maxillary sinus septa, their height, size, localization in order to prevent complications during surgical interventions.MATERIAL AND METHODS. The article analyzes CBCT data from 444 patients for the presence of septa in the area of the lower wall of the maxillary sinus. The subjects were divided into two groups: with the presence of premolars and molars (288 CBCT) and with the absence of at least one chewing tooth (156 CBCT). A study of 48 passportized skulls was conducted, the anterior wall of the maxillary sinus was sawed out, the structure of the sinus floor and septa was studied in detail. The ratio of the volume of compact and spongy bone substance in the premolar and molar areas was also measured.RESULTS. The obtained research data allowed us to obtain new information about the number of septa in the case of a complete dentition and partial tooth loss. Due to changes in the processes of sinus pneumatization, the number of septa increases with partial tooth loss. Their presence increases the risk of perforation of the Schneiderian membrane during sinus lift surgery, including the use of scaffolds based on a collagen matrix. However, when installing an implant in the base of the septum, its stability can be ensured, since the septa are some kind of buttresses of the maxillary bone. The ratio of the volume of spongy and compact bone substance in the premolar and molar area changes with age.CONCLUSION. The study found that the presence of coronal septa can cause complications of sinus lift surgery in the form of perforation of the Schneiderian membrane. At the same time, septa, being buttresses of the maxillary bone, can serve as a basis for installing an implant. With partial loss of teeth, the number of coronal septa increases. With age, the ratio of spongy and compact bone substance changes, towards a decrease in the volume of trabecular and an increase in the volume of compact bone.